The Cultural Communication In Society Values Pendalungan Jember - Pratiwi, Endah; Wibowo, Kunto Arief (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
The article tries to determine the consider of Pendalungan. of Pendalungan culture,look at communication and multicultural values of Pendalungan culture in Jember Regency . This consider was a qualitative descriptive method. The results showed that 1) there is cultural hybridization with a mixture of new and unique cultures; 2) Communication is carried out with Javanese and Madurese dialects with special dialects and 3) Multicultural values ​​are related to the geographical location of the residence concentric with circles of cultural gradation.